Ramsden, P. "Learning to Teach in Higher Education" - de la Cruz Tomé, Mª África (Tarbiya, Revista de Investigación e Innovación Educativa, 1993)
Reseña de "Learning to Teach in Higher Education" de P. Ramsden / New York: Routledge, 1992.